Intracystic haemorrhage in a non-endometriotic Mullerian vaginal cyst: an unexpected phenomenon - Ng, Beng Kwang; Lim, Pei Shan; Shafiee MN,; Abdul Kadir AK,; Nordashima Abd Shukor,; Omar MH, (Faculty of Medicine, UKM Medical Centre, 2016)
We report a case of rare, Mullerian vaginal cyst with intracystic haemorrhage in the absence of endometrial components. To date, this is the second case reported in the literature. A 51-year-old post-menopausal woman with history of anterior vaginal wall cyst was misdiagnosed to have cystocele. The cyst was excised and the content was old blood mixed with mucous. Histopathological examination revealed a Mullerian vaginal cyst without endometrial component. Thus, diagnosis and management of vaginal cyst was revisited and discussed.